Novel Pathogenic Variant in TGFBR2 Confirmed by Molecular Modeling Is a Rare Cause of Loeys-Dietz Syndrome - Michael T. Zimmermann; Raul A. Urrutia; Patrick R. Blackburn; Margot A. Cousin; Nicole J. Boczek; Eric W. Klee; Colleen Macmurdo; Paldeep S. Atwal (Case Reports in Genetics)
Loeys-Dietz syndrome (LDS) is a connective tissue disorder characterized by vascular findings of aneurysm and/or dissection of cerebral, thoracic, or abdominal arteries and skeletal findings. We report a case of a novel pathogenic variant in TGFBR2 and phenotype consistent with classic LDS. The proband was a 10-year-old presenting to the genetics clinic with an enlarged aortic root (Z-scores 5-6), pectus excavatum, and congenital contractures of the right 2nd and 3rd digit. Molecular testing of TGFBR2 was sent to a commercial laboratory and demonstrated a novel, likely pathogenic, variant in exon 4, c.1061T>C, p.(L354P). Molecular modeling reveals alteration of local protein structure as a result of this pathogenic variant. This pathogenic variant has not been previously reported in LDS and thus expands the pathogenic variant spectrum of this condition.